Self-Isolation in MIMO Microstrip Patch Arrays Using Annular Via-Based Mode Conversion - Manzoor Elahi; Slawomir Koziel; Leifur Leifsson (IEEE Access, 2025)
This paper presents a novel self-isolation technique for multiple-input multiple-output (MIMO) microstrip patch antenna (MPA) arrays using annular via-based mode conversion. The proposed approach transforms the TM20 mode into a hybrid TM20+TM01 mode, enabling high isolation in both E-plane and H-plane coupled configurations without requiring additional decoupling structures. A compact $2× 1$ single-fed antenna array is designed using annular vias and an open slot in the MPA, serving as a fundamental unit for the MIMO array. By exciting an element with a hybrid mode in the H-plane coupled MIMO array, a TM10 mode of very low intensity is induced on the adjacent half and a TM01 mode on the rear half of the nearby patch that leads to high isolation. However, in the E-plane coupled MIMO array a quasi-TM01 mode is induced on each half of the nearby patch whose overall field distribution resembles a TM11 mode due to the slot in the patch and the annular vias. Thus, in both configurations, the coupled modes are either orthogonal or exhibit weak field distribution concerning the excited mode. To validate the technique, $2× 1$ MIMO arrays were fabricated and measured. An isolation levels of 38 dB and 40 dB is demonstrated in the E-plane and H-plane configurations, respectively, at 5.8 GHz. The measured cross-polarization level is −50 dB in the broadside direction for the E-plane coupled array in both planes and it is 18 dB/23 dB at $φ =0^{° } $ / $φ =90^{° } $ in the H-plane array. Additionally, a broadside gain of 7.3 dB and 7.1 dB is achieved for a single port in the respective configurations. The proposed technique offers an effective, scalable, and space-efficient solution for high-isolation MIMO antenna systems, making it suitable for advanced wireless communication applications.